Preventing Weight Gain and Obesity: Indirect Effects of the Family Check-Up in Early Childhood - Smith, Justin D. (Prev Sci, 2015)
The early signs of obesity are observable in early childhood. Although the most promising prevention approaches are family centered, few relevant early prevention programs exist. This study evaluated the effects of an evidence-based, home-visiting intervention, the Family Check-Up (FCU), on the trajectory of children’s weight gain. The FCU was designed to prevent the development of behavior problems by improving family management practices; children’s weight has not been an explicit target. On the basis of previous research and conceptual models, we hypothesized that intervention effects on parenting practices, specifically caregivers’ use of positive behavior support (PBS) strategies in toddlerhood, would mediate improvements in children’s weight trajectories. A total of 731 indigent caregiver–child dyads from a multisite randomized intervention trial were examined. Observational assessment of parenting and mealtime behaviors occurred from age 2 to 5. The child’s body mass index (BMI) was assessed yearly from age 5 to 9.5. Path analysis with a latent growth model revealed a significant indirect effect of the FCU on the trajectory of BMI in later childhood. Improvements in caregivers’ PBS in toddlerhood, which was related to the nutritional quality of the meals caregivers served to the child during the mealtime task, served as the intervening process. Further, findings indicate that the FCU prevents progression to overweight and obese status amongst at-risk children. These study results add to existing evidence that has demonstrated that family-based interventions aimed at improving general family management skills are effective at preventing weight gain. Future directions are discussed.